2018
DOI: 10.1038/s41419-018-0747-y
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer chemotherapy and radiotherapy trigger both non-cell-autonomous and cell-autonomous death

Abstract: Even though cell death modalities elicited by anticancer chemotherapy and radiotherapy have been extensively studied, the ability of anticancer treatments to induce non-cell-autonomous death has never been investigated. By means of multispectral imaging flow-cytometry-based technology, we analyzed the lethal fate of cancer cells that were treated with conventional anticancer agents and co-cultured with untreated cells, observing that anticancer agents can simultaneously trigger cell-autonomous and non-cell-aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 39 publications
(50 reference statements)
0
31
0
Order By: Relevance
“…Entosis was described as cannibalism by cancer cells in culture after loss of substrate adherence, sometimes resulting in death of the engulfing cell and sometimes lysosomal degradation of the engulfed cell (Overholtzer et al, 2007; Krishna and Overholtzer, 2016). Rates of entosis can be increased by glucose starvation (Hamann et al, 2017) or 12–48 h after radiation/chemotherapy treatment (Martins et al, 2018). Breast cancer cells in 3D culture were shown to engulf bone marrow–derived mesenchymal stem/stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Entosis was described as cannibalism by cancer cells in culture after loss of substrate adherence, sometimes resulting in death of the engulfing cell and sometimes lysosomal degradation of the engulfed cell (Overholtzer et al, 2007; Krishna and Overholtzer, 2016). Rates of entosis can be increased by glucose starvation (Hamann et al, 2017) or 12–48 h after radiation/chemotherapy treatment (Martins et al, 2018). Breast cancer cells in 3D culture were shown to engulf bone marrow–derived mesenchymal stem/stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…9559L, Cell Signaling) (6,15,25), cleaved caspase-3 (1:1,000, catalog no. 9661L, Cell Signaling) (24,53,55), and ␤-actin (as a loading control, 1:1,000, catalog no. 4967L, Cell Signaling) (12,32,54) for 3 h at room temperature or overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…72 Consistent with the immunosuppressive activity of IDO in this setting, ex vivo stimulation of peripheral blood cells with 1-MT increased T cell responses to vaccination. 72 Recently, Hu et al also demonstrated that a methyltryptophan-paclitaxel (MP) albumin-bound drug conjugate (that links indoximod to the microtubular poison paclitaxel [74][75][76][77] through an ester bond) not only significantly elevates the tumor levels of indoximod and local CD8 + T populations, but reduces granulocyte-like myeloid derived suppressor cells (G-MDSCs) and T REG cells. 78…”
Section: Indoximodmentioning
confidence: 99%